2018
DOI: 10.3889/oamjms.2018.232
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors Diminish Barrett's Esophagus Length: Our Experience

Abstract: AIM:Our main objectives were to evaluate the influence of two-year proton pump inhibitors (PPI) therapy in patients with Barrett’s oesophagus on its length, in both types, short and long segment.METHODS:In this single-centre, prospective interventional controlled study were analysed data collected prospectively over two years from patients with Barrett’s oesophagus diagnosed by endoscopy. Patients who received continuous proton pump inhibitors (PPI) for 2 years were included. At each patient visit symptoms wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Heartburn and esophageal reflux were observed in 8 of the 12 cases. Gashi et al [18] reported that BE shortened the maximum length and total circumference when proton pump inhibitors (PPIs) were administered for 2 years. As such, PPIs may be effective in patients with reflux esophagitis and GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Heartburn and esophageal reflux were observed in 8 of the 12 cases. Gashi et al [18] reported that BE shortened the maximum length and total circumference when proton pump inhibitors (PPIs) were administered for 2 years. As such, PPIs may be effective in patients with reflux esophagitis and GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Acid-suppressive therapy during the early stages of BE or ablative surgery and acid-suppressive therapy at advanced stages are the only recommendations for medical management of BE, although their efficacy in preventing EA remains questionable. Acid-suppressive therapy and anti-reflux surgery reduce exposure of the esophagus to acidic contents of the stomach (Gore et al, 1993;Peters et al, 1999;Weinstein, 2002;El-Serag et al, 2004;Gashi et al, 2018;Tan et al, 2018). Although, in most cases, the change in length of the BE segment is reportedly uncommon, the acid suppression prevents disease progression during these early stages of BE.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the effects of PPI treatment on esophageal and gastric mucosal inflammation in SSc patients are heterogeneous. PPI treatment with maximal doses (lansoprazole 2 × 30 mg or pantoprazole 2 × 40 mg) is useful for long-term safety and reduces the length of Barrett esophagus (29). Some other reports suggested that patients with SSc should be encouraged to receive early and long-term PPI treatment (14,19).…”
Section: Discussionmentioning
confidence: 99%